Methodology of character education (The Peerian Journal, 2023)
this article provides information on the methodology of teaching Khusnihat, the basic principles of Khusnihat teaching methodology, the benefits of Khusnihat teaching methodology, the implementation of Khusnihat teaching methodology in the textbook